Margaret Visser: Much Depends on Dinner - Brown, Lynda (Petits Propos Culinaires, 1990)
Margaret Visser: Much Depends on Dinner: Penguin Books, 1989: 351 pp, bibliographical references: index, paperback, £7 .95.